Aventuras de una negrita en busca de Dios - Shaw, Bernard, 1856-1950; Gómez Ibáñez, Benito; Farleigh, John, 1900-1965; Shaw, Bernard, 1856-1950. (Barcelona : Galaxia Gutenberg : Círculo de Lectores, 2014)
Shaw caught a ton of grief for this 1932 novel. The protagonist is an African native girl recently converted to Christianity. She goes in search of God, literally walking into the bush to seek her maker. Instead, she finds numerous religious figures and philosophers, ranging from Noah to Voltaire.
Translated from the English: The adventures of the black girl in search of God. London : Constable & company limited, 1932.
Online resource; title from PDF title page (Digitalia, viewed August 10, 2014)
Keywords: Christianity -- Fiction; Christian fiction; Electronic books